Effect of Knowledge Sharing Mediation on Employee Performance Efarina Hospital Employee - Adrian K Tarigan; Imelda Gultom (Institute of Computer Science (IOCS), 2020)
This study aims to find out the positive and significant influence between knowledge sharing mediation on the performance of employees of the Health Office of Efarina Pangkalan Kerinci Hospital. The population of this study is all employees of worker Efarina Pangkalan Kerinci Hospital of 280 people. The sample was taken as much as 15% of the total population of 42 people. Knowledge sharing variables are measured by knowledge donating and collecting, while employee performance variables are measured by work quality, quantity of work, job knowledge, cooperation, reliable, initiative, and personal quality. This research method is a quantifying method. Data collection in this study was conducted by providing Knowledge Sharing questionnaires and employee performance to the parties concerned. The result of the data regression analysis, it is known that there is a linear relationship of Mediation Knowledge Sharing (X1) to Employee Performance (Y), as evidenced by the R Square (R2) value of 0.663 or 66.3% which means that 66.3% of knowledge sharing variables can be explained by employee performance variables or have an influence of 66.3% on the performance of employees of Efarina Pangkalan Kerinci Hospital. Then, hypothesis obtained that the knowledge sharing variable has a value of tHitung 8.72 > tTabel 2.02.